DINÓPOLIS: learning paleontology (Journal of Parents and Teachers, 2014)
Dinópolis is a theme park in Teruel that aims to bring Paleontology in an entertaining way and enhance that almost magical aspect that has everything related to life on our planet for millions of years.
Keywords: theme park; paleontology; time travel; T-Rex